Tracking variations of fluorescent dissolved organic matter during wastewater treatment by accumulative fluorescence emission spectroscopy combined with principal component, second derivative and canonical correlation analyses. (March 2018) - Guo, Xujing; Yu, Huibin; Yan, Zongcheng; Gao, Hongjie; Zhang, Yizhang
Abstract: Accumulative fluorescence emission (AFE) spectroscopy combined with principal component analysis (PCA), second derivative and canonical correlation analysis (CCA) was firstly developed into an available tool to track variations in dissolved organic matter (DOM) fractions and contents during wastewater treatment. Samples were collected from a wastewater treatment plant with a traditional anaerobic/anoxic/oxic (A2O) process. The AFE spectroscopy deduced from the sum of intensities along the excitation wavelengths of fluorescence excitation emission matrix (EEM), could distinctly track tyrosine-like, tryptophan-like, fulvic-like substances. The AFE spectroscopy with the PCA not only disaggregated DOM fractions into the tyrosine-like, tryptophan-like, microbial humic-like, fulvic-like and humic-like substances, but discriminated DOM fractions from the physical sedimentation, anaerobic/anoxic and oxic processes. Absolute areas of fluorescence components obtained by the second derivative AFF spectra had positive liner correlations with Fmax of the relevant components modeling from EEM-PARAFAC, especially the tryptophan-like ( R 2 = 0.95, p < 0.01) and tyrosine-like ( R 2 = 0.83, p < 0.01) substances. The CCA of the sites presented that the potential factors contained the tryptophan-like and tyrosine-like substances. This indirectly proved that the tryptophan-like and tyrosine-like substances were the dominant components of fluorescent DOM, which were further removed in A2O than the other fluorescent components. The CCA of the fluorescent components exhibited that the potential factors included the sites #1 to #6, which were located in the original wastewater, sand setting, primary sedimentation, anaerobic, anoxic, facultative units. This elaborated that the fluorescent components were mainly degraded in the physical sedimentation, anaerobic and anoxic processes. Graphical abstract: Highlights: Define AFE spectroscopy compared with synchronous spectroscopy to characterize DOM fractions. Employ AFE spectroscopy coupled with PCA to reveal DOM variations. Develop second derivative AFE approach compared with EEM-PARAFAC to track components and contents of DOM.